Hubungan Antenatal Care (ANC) Dengan Kejadian Stunting Di Puskesmas Sumbang Kabupaten Enrekang (Window of Public Health Journal, 2026)
Antenatal Care (ANC) is a form of health service provided to pregnant women before giving birth, with the aim of building trust, detecting potential complications, preparing for childbirth, and providing health education. This study aims to determine the relationship between Antenatal Care (ANC) and the incidence of stunting at the Sumbang Community Health Center, Enrekang Regency. This study uses a quantitative research method with a cross-sectional approach. The sampling method in this study uses a random sampling technique with sampling using the Slovin formula, so that the number of samples in this study is 175 mothers who have toddlers aged 0-60 months in the working area of ​​the Sumbang Community Health Center, Enrekang Regency. The data analysis used is univariate analysis and bivariate analysis. According to the results of the bivariate analysis using the chi-square test, it shows that two variables, namely the Frequency of Antenatal Care Visits (p = 0.000